Methylation profiling in neuropathological tumors diagnosis: a comprehensive review - Al Sharie, Sarah; Sawaftah, Khaled; Qasim, Hussein; Al-Hussaini, Maysa (Frontiers in Oncology, 2025)
DNA methylation profiling has emerged as a transformative tool in the diagnosis and classification of central nervous system (CNS) tumors. Traditional approaches like histology, immunohistochemistry, and targeted molecular testing cannot fully capture the biological and clinical diversity of these neoplasms. In contrast, genome-wide methylation analysis provides highly reproducible epigenetic “fingerprints” that reflect both lineage and oncogenic alterations, enabling objective tumor classification, refinement of existing categories, and discovery of novel entities. This comprehensive review summarizes the principles of DNA methylation, available platforms, and the application of methylation-based classifiers across major CNS tumor groups, including diffuse gliomas, medulloblastomas, ependymomas, and meningiomas. We highlight how methylation profiling complements other molecular techniques by simultaneously generating copy number profiles and promoter methylation data, consolidating multiple diagnostic assays into a single platform. Practical considerations such as tissue quality, bioinformatic pipelines, interpretation thresholds, and cost are addressed, as are comparisons with sequencing, RNA expression, and immunohistochemistry. Finally, we explore future directions, including nanopore-based rapid testing, liquid biopsy, and artificial intelligence, which promise to extend the reach and clinical utility of methylation profiling. Collectively, these advances are establishing DNA methylation analysis as a cornerstone of precision neuropathology, aligning diagnostic and prognostic assessment with tumor biology to improve patient care.